Bovine brucellosis in Codo del Pozuzo district, Huanuco - Zavala D., Imelda (2011)
A seroprevalence study on 5439 cattle from April to June 2007 was conducted based on a circumstantial diagnosis of two cases of bovine brucellosis in the district of Codo del Pozuzo, en the region of Huanuco. Two animals resulted positive to the Rose Bengal test but negative to the Complement Fixation test. The beta distribution using a simulation model showed a prevalence of 0.02% with a minimum interval of confidence of 0 and maximum of 0.06%.